3520 Neural connectivity mechanisms linking off-time pubertal development and depression risk in adolescence. (27th March 2019) - Chahal, Rajpreet; Marek, Scott; Vilgis, Veronika; Weissman, David; Hastings, Paul; Robins, Richard; Guyer, Amanda E.
Abstract : OBJECTIVES/SPECIFIC AIMS: Earlier pubertal timing has been associated with risk for depression, particularly in girls (e.g., Keenan etal., 2014). Evidence suggests pubertal timing in girls also relates to alterations in the microstructural properties of brain white matter tracts in late adolescence (Chahal etal., 2018), and structural connectivity of cingulate and frontal regions (Chahal etal., in prep), though differences in pubertal development in both boys and girls have not been examined in the context of brain functional connectivity (FC). Individual differences in the course of puberty may have enduring effects on functional coupling among brain regions that may contribute to the risk for psychopathology. To address this question, we explored the relation between pubertal timing and tempo with depression symptoms (age 16). Then, we examined whether brain network FC (age 16) associates with pubertal indices and predicts concurrent and later depressive symptoms (age 18). METHODS/STUDY POPULATION: Sixty-eight adolescents (37 females) completed the Mini-Mood and Anxiety Symptom Questionnaire (MASQ; Clark & Watson, 1995) at ages 14-18. Gompertz growth curve modelling of pubertal development (age 10-15; Waves 1-6) was used to estimate pubertal timing and tempo per individual, separately for males and females (e.g., Chahal etal., 2018). Resting-state MRI data (age 16) were parcellated into 264 cortical and subcortical regions to create region-to-region FC matrices based on correlations of time-series. Individual matrices were fed to the GraphVar program (Kruschwitz etal., 2015) to assess the interaction of pubertal timing and pubertal tempo with functional network connectivity using Network-based statistic (NBS; Zalesky etal., 2010). Subnetworks showing alterations in relation to pubertal timing and tempo were then examined in association with concurrent (age 16) symptoms and used to predict future depressive symptoms (age 18). RESULTS/ANTICIPATED RESULTS: In all youth, earlier pubertal timing was associated with higher depressive symptoms at age 16 (p<.018). This association was stronger in girls with slower pubertal tempo (p<.039). Interregional connectivity analyses revealed that the interaction of earlier pubertal timing and slower tempo was associated with lower FC between the left cingulate gyrus and right precuneus (p<.0001), regions implicated in emotion processing (i.e., Affective Processing Network) and self-referential thinking (i.e., Default Mode Network). FC of the three other emotion- and self-referential processing network regions (i.g., left insula, superior parietal lobule, and precuneus) was lower in youth with greater age 16 depressive symptoms (p<.0001). Finally, lower FC of of the left and right inferior parietal lobule predicted greater depressive symptoms at age 18 (p<.0001). In summary, FC of overlapping affective and default mode network areas was related to earlier pubertal timing and higher concurrent and future depressive symptoms. DISCUSSION/SIGNIFICANCE OF IMPACT: These findings demonstrate individual differences in pubertal maturation are associated with depressive symptoms and differences in brain connectivity in mid-adolescence. Early pubertal development was associated with greater depression symptoms and lower FC of brain regions involved in emotion regulation and self-referential processing. Further, FC between these regions predicted higher depression symptoms two years later. These neurobiological mechanisms may, in part, underlie the link between off-time pubertal development and the risk for depression. These findings also have important implications for precision psychiatry, as we show that a risk-factor of depression (early pubertal timing) may manifest in developing neurobiology in region-specific ways. Previous network models of depression (e.g., Li etal., 2018) implicated affective network connectivity in sustained negative mood and the default mode/ self-referential network in rumination. Other networks implicated in these past models include the reward network, which may be involved in anhedonia and loss of pleasure. Our study only found associations between affective and self-referential regional connectivity, pubertal maturation, and depression, suggesting that pubertal risk factors may relate more closely with emotion-regulation and self-referential processing deficits.